The Effect of Place Attachment On The Satisfaction and Loyalty of Tourists Visiting The Coffee Shop In Kintamani, Bangli Regency, Bali - Agus Radita, I Gede; Adikampana, I Made; Antara, I Ketut (Devotion : Journal of Research and Community Service, 2023)
The COVID-19 pandemic has been happening since 2019, and the tourism industry is one of the affected industries. Bali is one of the affected places because most of the people work in the tourism industry, but on the other hand when the Covid-19 pandemic takes place there is one place in Bali that is still crowded with tour-ists. Kintamani is one of the places that is still crowded with tourists, especially at the coffee shop in Kintamani, because it has beautiful and exotic views of the lake and Mount Batur. This study aims to find out whether there is an influence of place attachment that makes tourists loyal apart from satisfaction. The data col-lection technique in this study used a questionnaire, then the sample determina-tion technique used purposive sampling, namely determining respondents based on certain criteria, in this study the sample referred to was tourists who had vis-ited the coffee shop in Kinatamani at least 2 times. The data analysis technique used in this research is descriptive quantitative, then hypothesis testing using smart PLS software. The results of this study concluded that based on the t test, the t-statistical value obtained from each varibel has a value of more than 1.98 which is the standard value of measuring the significance of the t-statistical influ-ence of  each variable in this study, which means that there is a positive direct influence between place attachment  (X) on satisfaction (Y1),  satisfaction (Y1) on loyalty (Y2),   place attachment  (X) to loyalty (Y2) and the indirect influence that satisfaction (Y1) is able to mediate place attachemnt  (X) and loyalty (Y2).